Represent : art and identity among the black upper-middle class - Banks, Patricia Ann (Routledge research in race and ethnicity, 2010)
Examines how upper-middle class blacks forge black identities for themselves and their children through the consumption of black visual art. This book documents how the salience of race extends into the cultural life of even the most socioeconomically successful blacks.